2022
DOI: 10.1111/exd.14660
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteomic expression in indolent vulvar lichen sclerosus, transforming vulvar lichen sclerosus and normal vulvar tissue

Abstract: Vulvar lichen sclerosus (VLS) confers approximately 3% risk of malignant transformation to vulvar squamous cell carcinoma (VSCC). We used unbiased proteomic methods to identify differentially expressed proteins in tissue of patients with VLS who developed VSCC compared to those who did not. We used laser capture microdissection-and nanoLC-tandem mass spectrometry to assess protein expression in individuals in normal vulvar tissue (NVT, n = 4), indolent VLS (no VSCC after at least 5 years follow-up, n = 5) or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…We used formalin‐fixed paraffin‐embedded (FFPE) oral mucosal biopsies from the aforementioned patients for mass spectrometry. We utilized a previously published method for extracting the proteins and subjecting them to proteomics analysis 11,12 . In brief, 10‐μm‐thick sections were obtained for each patient and stained with haematoxylin‐and‐eosin (H&E).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used formalin‐fixed paraffin‐embedded (FFPE) oral mucosal biopsies from the aforementioned patients for mass spectrometry. We utilized a previously published method for extracting the proteins and subjecting them to proteomics analysis 11,12 . In brief, 10‐μm‐thick sections were obtained for each patient and stained with haematoxylin‐and‐eosin (H&E).…”
Section: Methodsmentioning
confidence: 99%
“…We utilized a previously published method for extracting the proteins and subjecting them to proteomics analysis. 11,12 In brief, 10μm-thick sections were obtained for each patient and stained with haematoxylin-and-eosin (H&E). Unstained sections of the same thickness were mounted on polyethylene naphthalate (PEN) membrane slides for laser pressure catapulting to collect tissue (Zeiss Microbeam).…”
Section: F I G U R Ementioning
confidence: 99%
“…The blood supply can be improved and nutrition of the skin can be increased in the local nonneoplastic lesions of vulvar epithelium ( 17 , 18 ). Local scratching-damaged tissue can be repaired to maintain the integrity and elasticity of vulvar skin ( 19 ). In our study, we found that both treatments were clinically more effective for both types of lesions; the overall efficacy at 1, 3, and 6 months after treatment was above 50%, with the laser treatment group experiencing the most pronounced effect.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic profiles of these NVT and VLS samples were previously published by our team in a study examining malignant transformation in VLS. 12 OLP and NOM samples were also previously published in a study of carcinogenesis in OLP. 13 There were insufficient VLP samples associated with development of vulvar SCC to address the question of malignant transformation for VLP.…”
Section: Patient Selectionmentioning
confidence: 99%
“…We utilized a previously published method for extracting the proteins and subjecting them to proteomics analysis. 12,13,17 In brief, 10 μm-thick sections were obtained for each patient and stained with haematoxylin-and-eosin (H&E). Unstained sections of the same thickness were mounted on polyethylene naphthalate (PEN) membrane slides for laser pressure catapulting to collect tissue (Zeiss Microbeam).…”
Section: Tissue Collectionmentioning
confidence: 99%